Sleep Duration and Sleep Hygiene Among Rural and Urban Residents in District Etawah of Uttar Pradesh: A Community Based Comparative Cross-sectional Study - Rajarao, Tamma; Jain, Pankaj Kumar; Srivastava , Dhiraj Kumar; Raheja, Lokesh; Gola, Mukesh Kumar; Kumar, Atul; Takhelchangbam, Nilima Devi; Devi, Billa P S Sree (Indian Journal of Community Health, 2024)
Background: Sleep deprivation include physical effects (sleepiness, fatigue) cognitive impairment (deterioration of performance, attention and motivation) and mental health issues. Objectives: To assess and compare sleep duration and sleep hygiene with their associated factors among rural and urban residents of a district of Uttar Pradesh. Material and Methods: This cross?sectional study was conducted in Etawah district, UP, from January 2022 to June 2022. All residents of rural and urban areas were included using multistage sampling. Study tool included a questionnaire which collected sociodemographic information, sleep duration, and sleep hygienic practices using sleep hygiene index. Results: In this study, 240 participants each from the rural and urban areas were included. The mean duration of sleep among the participants in rural and urban areas was 7.40±1.22 and 8.18±1.30 h during the workdays whereas, 7.30±1.30 and 8.11±1.35 h during the weekends respectively. About 40% were having unhygienic sleep practices. Most of the study participants had the history of sleep duration less than 8 hr. among the comparison groups. Graduated participants had the more sleep problems. Conclusions: Particularly among the elderly, inadequate sleep duration and differences in sleep rhythm between weekdays and weekends were seen.